2013
DOI: 10.1136/annrheumdis-2013-eular.1926
|View full text |Cite
|
Sign up to set email alerts
|

SAT0200 Abnormal Cardiac SPECT/CT in Newly Diagnosed, Untreated Patients with Idiopathic Inflammatory Myopathies

Abstract: Background Knowledge of cardiac involvement in idiopathic inflammatory myopathies (IIM) is limited and a matter of debate with reported frequencies between 6% and 75%. Although clinically overt disease is rare, cardiac events are the major cause of death in IIM. No studies of the heart by SPECT/CT in newly diagnosed, untreated adults with IIM have been performed. Objectives To examine cardiac involvement in newly diagnosed, untreated patients with IIM by cardiac SPECT/CT imaging compared to a gender- and age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…QTc duration reflects the ventricular repolarization period and a prolonged QTc indicates a slowed ventricular repolarization, which is linked to increased risk of ventricular arrhythmias and sudden death (9)(10)(11). We have shown longer mean QTc intervals and more frequently left ventricular diastolic dysfunction in a cohort of patients with PM/DM compared to healthy controls (HCs) (3). Presence of myositis-specific autoantibodies (MSAs) or myositis-associated autoantibodies (MAAs) was associated with diastolic dysfunction, although no relationship between any specific autoantibody and cardiac function was found, probably due to the low number of patients with each autoantibody.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…QTc duration reflects the ventricular repolarization period and a prolonged QTc indicates a slowed ventricular repolarization, which is linked to increased risk of ventricular arrhythmias and sudden death (9)(10)(11). We have shown longer mean QTc intervals and more frequently left ventricular diastolic dysfunction in a cohort of patients with PM/DM compared to healthy controls (HCs) (3). Presence of myositis-specific autoantibodies (MSAs) or myositis-associated autoantibodies (MAAs) was associated with diastolic dysfunction, although no relationship between any specific autoantibody and cardiac function was found, probably due to the low number of patients with each autoantibody.…”
Section: Introductionmentioning
confidence: 94%
“…The most common subgroups are polymyositis (PM), dermatomyositis (DM), inclusion body myositis (IBM), antisynthetase syndrome (ASS), and immune mediated necrotizing myopathy (IMNM) (2). IIM is characterized by multisystem involvement which is associated with a poor outcome (1,3). Heart involvement is a significant cause of death in patients with PM or DM, already in the first year after diagnosis of IIM, yet, cardiac symptoms are often subclinical and may be overlooked (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMR was the most useful diagnostic modality ( Fig. 2 ) [ 8 ]. Similarly, our finding that approximately a third of patients with a diagnosis of probable/definite (peri)myocarditis had abnormalities on parametric T1/T2-mapping in CMR, but not with conventional LGE on CMR, is in accordance with earlier reports [ 2, 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the number of reports concerning heart involvement in IIMs have increased as more sensitive, invasive, or noninvasive techniques were used to detect this extra-skeletal muscular involvement. [3][4][5][6][7] A few observational studies based on objective evidence of diseased heart have demonstrated that the incidence for cardiac involvement approximately was 9% to 72%, and those patients with diseased heart had worse prognosis, and cardiac manifestation was a major cause of deaths. [8][9][10][11] Hence, early identification for cardiac involvement may help improve the management and clinical outcomes of these patients, but currently, the diagnostic strategy is lacking.…”
mentioning
confidence: 99%